IT’S EXHAUSTING TO CREATE AN EVENT OUT OF NOTHING: Slow Violence and the Manipulation of Time - AHMANN, CHLOE (Cultural anthropology, 2018)
In recent years, scholars have developed a vocabulary for describing scenes of insecurity, precarity, and disorder too slow to achieve recognition as crises. Concepts such as slow violence, for example, depend on forms of delay, deferral, attrition, and accumulation whose ordinariness exacerbates suffering. But not enough attention has been paid to how those mired in the experience of protracted harm themselves use time to respond to this pernicious condition. In this article, I focus on the deliberate manipulations of time that characterize responses to slow violence by examining a campaign to halt the construction of a trash incinerator in south Baltimore. The incinerator—which posed toxic risk for residents in exchange for the promise of clean, green, renewable energy—was to be the latest in a steady stream of impositions that have plagued local bodies since the nineteenth century. Here, I scrutinize this history and the consequences of gradual industrial incursion on risk perceptibility. I then analyze the ways in which time has been slowed, sped up, reordered, and strategically punctuated by parties on multiple sides of the incinerator campaign. In the process, this article offers up a set of tools that, beyond depicting time as a medium of violence, also specify temporalities of resistance and refusal. Taken together, they suggest that slow violence, rather than merely obstructing response, invites creative forms of temporal orchestration and moral punctuation.